Hubungan Antara Konsep Diri Dengan Kecemasan Memperoleh Pasangan Hidup Pada Wanita Dewasa Awal - Emiliana Luh Damayanti; Endah Cahya (NERSMID : Jurnal Keperawatan dan Kebidanan, 2020)
Anxiety in obtaining a life partner is a manifestation of various feelings both physically and psychologically such as feelings of fear, worry, anxiety, tension, and lack of confidence in getting a mate or partner as a place of sharing and biological fulfillment and physiology. The concept of self is the perception of an individual about himself through assessment, hope, and knowledge of himself in terms of physical, social, and psychological. Self-concept makes individuals evaluate their weaknesses and strengths. In addition, the concept of self directs the individual in acting and the formation of his personality.This study aims to determine the relationship between self-concept and anxiety in obtaining a life partner in early adult women. The subjects of this study were UNTAG Surabaya students aged 18-40 years with 61 subjects. The hypothesis in this study is "there is a relationship between self-concept and anxiety about getting a life partner in early adult women". The research data was collected using a Likert scale from the anxiety scale to obtain a life partner and self-concept scale. The research data were analyzed by simple regression correlation statistics using version 21 Statistical Package for Social Science (SPSS) program. The results of the analysis stated that the hypothesis was accepted (F = 6,363) at p 0,030 (p